Frequent hypomethylation of PTGS2 gene promoter in human term placenta - Mohammad, Nuruddin; Yaqinuddin, Ahmed; Kakal, Fatima; Sheikh, Luman; Qureshi, Rahat; Somani, Mehreen (Italian Journal of Anatomy and Embryology, 2013)
Background: Gene expression profiles of several tumor suppressor genes are regulated by the methylation and demethylation of their promoters. Here, we aim to identify and quantify the methylation status of four tumor suppressor genes from placentas at term and compare them with the maternal white-blood-cells. Methods: In order to achieve this objective, DNA enriched from twenty placentas at term and maternal white blood cells was bisulfite-converted and amplified using quantitative real-time methyl-light polymerase chain reaction for the four-genes studied (RASSF1A, APC, RAR-beta, and PTGS2). Results: Among the four genes examined, RASSF1A, APC and RAR-beta promoter regions were hypermethylated in all the placental samples compared with maternal WBCs. Strikingly, PTGS2 was found to be hypomethylated in the placentas compared to the maternal cells. Conclusion: Since placental DNA represents fetal methylation profile and it is an established fact that there is certain amount of cell free circulating DNA in human plasma/serum, these data strongly suggest that hypermethylation of RASSF1A, APC and RAR-beta can be used as gender independent biomarkers to distinctly identify placental DNA in maternal blood. In-addition, this is the first report which demonstrates hypomethylation of PTGS2 locus which may have important clinical implications e.g. placental abnormalities.